Single- and Multiple-dose Pharmacokinetic, Safety and Tolerability Study of Mildronate Injection in Healthy Chinese Subjects Pharmacokinetic of Mildronate Injection - Zhao, Z.; Chen, J.; Peng, W.; Wang, X.; Chen, Z.; Tang, H.; Liang, Y.; Ma, Z.; Chen, J.; Chen, X.; Zhong, G.; Huang, M. (Drug Research, 2016)
Mildronate is an agent for cardioprotection and neuroprotection. This study aimed to evaluate the pharmacokinetic (PK) profiles, safety and tolerability of mildronate injection after single escalating doses and multiple doses in healthy Chinese subjects. We performed a randomized, open-label, single- and multiple-dose phase I trial including 3 doses of mildronate: 250, 500 and 750 mg. Plasma and urine samples were collected and concentrations of mildronate were analyzed by liquid chromatography-mass spectrometry (LC-MS/MS). PK parameters were calculated using noncompartmental analysis. Safety and tolerability was assessed throughout noting subjects’ vital signs and monitoring adverse events (AEs) and conduct a comprehensive physical examination and laboratory analyses before and after the study. There was no significant difference in C0, AUC0-t, AUC0-∞ among 3 single-dose groups, whereas T1/2 had significant statistical difference which may be caused by the inhibition of metabolic enzymes. Single- and multiple-dose intravenous injection of mildronate exhibited linear PK profiles in the range of 250–750 mg. An unconspicuous accumulation phenomenon was found after multiple-dose mildronate administration. No significant gender difference was found and mildronate is primarily excreted by the kidney. No serious AEs were observed. The formulation was safe and well tolerated from 250 to 750 mg.
Keywords: healthy Chinese subjects; mildronate injection; pharmacokinetics study; safety; tolerability